2019
DOI: 10.1097/aog.0000000000003581
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Infant Health Care Costs Related to Preeclampsia

Abstract: Brown J, et al. Maternal and infant health care costs related to preeclampsia. Obstet Gynecol 2019;134. The authors provided this information as a supplement to their article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 16 publications
0
35
0
1
Order By: Relevance
“…Hypertensive disorders included both confirmed pre-eclampsia (one Irish and one US study [25,56]) and hypertension during pregnancy (three studies set in the US [30,37,56]), with all hypertension studies examining different costs (mothers only, children only or mother and children combined). Incremental costs per case for hypertension ranged from €2,860 to €8,595 (Table 4).…”
Section: Other Maternal Health Problemsmentioning
confidence: 99%
“…Hypertensive disorders included both confirmed pre-eclampsia (one Irish and one US study [25,56]) and hypertension during pregnancy (three studies set in the US [30,37,56]), with all hypertension studies examining different costs (mothers only, children only or mother and children combined). Incremental costs per case for hypertension ranged from €2,860 to €8,595 (Table 4).…”
Section: Other Maternal Health Problemsmentioning
confidence: 99%
“…Although close monitoring of pregnancies affected by or at high risk of HDP is recommended, the extent at which these women are being monitored and managed is not well understood, considering the high rates of mortality in Brazil and other LMICs. No surveillance data exist for monitoring and reducing the impact of HDP in these countries, and the burden of families affected by these conditions [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preeclampsia is a $2.18 billion (USD) per year problem, 23 and those pregnancies are 3 times more expensive than uncomplicated pregnancies, points we emphasized in an editorial and later studies confirmed. 24,25 As data from the MMRCs were reported in mainstream media, the court of public opinion helped fuel federal legislative efforts. The Foundation, working closely with partners (the ACOG, March of Dimes, Association of Maternal and Child Health Programs, and Society for Maternal-Fetal Medicine) and fueled by dozens of patient organizations, successfully shepherded the Preventing Maternal Deaths Act through a multiyear, bipartisan effort that President Trump signed into law in December 2018.…”
Section: Advocacymentioning
confidence: 99%